Factors associated with substance use among preclinical medical students in Turkey: A cross-sectional study - Karabacak, Mert; Kose, Ekin Beyza; Bahadir, Zeynep; Demirel, Yagmur; Mutlu, Elif Busra; Ozcan, Zeynep; Ozkara, Burak Berksu (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2024)
Introduction: Medical students experience high levels of stress due to their rigorous training, which can negatively affect their mental health. This study aimed to investigate substance use habits of medical students at Istanbul University-Cerrahpaşa and the association on their mental health and demographic factors.Methods: This cross-sectional survey study was conducted in March-April 2022 among preclinical medical students (years 1-3 of a 6-year program). A confidential, anonymous online survey consisting of four sections on sociodemographic and educational characteristics, nicotine use and dependence [Fagerström Test for Nicotine Dependence (FTND)], alcohol use [Alcohol Use Disorders Identification Test (AUDIT)], mental health status [12-item General Health Questionnaire (GHQ-12)], was distributed to 1131 students via WhatsApp and Telegram text messages. Mann-Whitney U and Kruskal Wallis tests compared variables’ distribution in the questionnaire categories. Spearman's correlation assessed associations between scales. Significance was p < 0.05.Results: The study included 190 medical students. A total of 26.3% of the participants were smokers, with 8.4% showing moderate to high levels of nicotine dependence. An estimated 45.8% and 8.4% reported low-risk consumption and risky usage of alcohol, respectively. There were statistically significant associations between substance use and demographic factors such as sex, GPA, and religious belief. The study found a statistically significant correlation between FTND scores and GHQ-12 scores, and, between FTND scores and AUDIT scores.Conclusion: The findings of this study will inform the development of interventions to improve the mental health and academic performance of medical students at Istanbul University-Cerrahpaşa. Furthermore, it will raise awareness about the importance of addressing substance use among medical students in Turkey.